1999
DOI: 10.1016/s0014-5793(99)01436-2
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and DNA‐binding properties of the rat pancreatic β‐cell‐specific factor Nkx6.1

Abstract: The homeodomain (HD) protein Nkx6

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 38 publications
1
33
1
1
Order By: Relevance
“…Although a requirement for Nkx6.1 in β-cell differentiation has been previously shown (Sander et al, 2000), our present study provides evidence that redundant activity of the NKX6.1 paralog NKX6.2 masks a more general (Awatramani et al, 2000;Jorgensen et al, 1999;Mirmira et al, 2000), and function both as transcriptional repressors through interaction with Gro/TLE co-repressor proteins . Second, when transfected into the developing neural tube, NKX6.1 and NKX6.2 have qualitatively similar activities in inducing motoneurons (Vallstedt et al, 2001).…”
Section: Discussionsupporting
confidence: 51%
“…Although a requirement for Nkx6.1 in β-cell differentiation has been previously shown (Sander et al, 2000), our present study provides evidence that redundant activity of the NKX6.1 paralog NKX6.2 masks a more general (Awatramani et al, 2000;Jorgensen et al, 1999;Mirmira et al, 2000), and function both as transcriptional repressors through interaction with Gro/TLE co-repressor proteins . Second, when transfected into the developing neural tube, NKX6.1 and NKX6.2 have qualitatively similar activities in inducing motoneurons (Vallstedt et al, 2001).…”
Section: Discussionsupporting
confidence: 51%
“…To focus our analysis on the role of Nkx6.1, a Pdx-1 negative cell system with over-expression of Nkx6.1 was used [28]. Transfection with Nkx6.1 induced a beta cell phenotype, associated with a small increase in insulin content (mRNA level and immunostaining) [28]. We demonstrated that induced Nkx6.1 expression alone in the Pdx-1 negative cells was able to further increase IL-1β sensitivity (Fig.…”
Section: Functional Analyses Of Pdx-1 and Nkx61 (Part Iii)mentioning
confidence: 88%
“…One based on the tetracycline-inducible stably transfected INS-1rαβ cells, with inducible expression of either Pdx-1 or a dominant-negative mutant form of Pdx-1 (DN-Pdx-1) [27]. The other cell system is the Pdx-1 and Nkx6.1 negative MSL-G-AN cells, stably transfected with Nkx6.1 (Nkx6.1 neg-ative clone 2 #584 and Nkx6.1 positive clone 3 #589 and clone 9 #624) [28].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations